Trends in Urban Research and Their Reflection in Slovak Ethnology/Anthropology - Bitušíková, Alexandra (Lidé města, 2010)
The study reflects the development of Slovak urban ethnology and anthropology since its beginning in the 1970s. It explores theoretical and methodological approaches toward the study of the city in the socialist and postsocialist periods and tries to find correlations with the development of urban anthropology in Western Europe and the United States. It mentions weaknesses and strengths of urban research results in Slovakia. The main emphasis of the paper is on the latest urban anthropological trends worldwide and their reflection in contemporary Slovak urban ethnological and anthropological research. Special attention is paid to three areas of current urban research: the problem of urban diversity; the problem of social production and construction of urban public space, and the problem of urban culture and local memory, identity and symbols.